Cold intolerance assessment: A reappraisal. (June 2014) - Davey, H; Belcher, HJCR
Introduction: The cold intolerance symptom severity (CISS) questionnaire is frequently used for the assessment of cold intolerance (CI) in patients following hand trauma. Its practical and conceptual limitations prompted the development of a new cold intolerance questionnaire (CIQ). The CIQ assesses and gives equal weighting to five components of CI, severity, frequency, extent, duration and prevention. An optional impact score can be included as the CIQ+. Method: Data were collected over a five-month period from adult hand trauma patients. Each patient completed the CISS, CIQ and the Quick DASH questionnaires during their assessment. A total of 51 patients (34 men and 17 women) were examined at a median interval of 14 months (3–48) after injury. Their mean age was 42 years (SE = 2, range 18–81). Results: The median (range) scores were CIQ = 16 (0–27), CIQ + = 18 (0–33), CISS = 56 (0–89) and Quick DASH = 44 (2–86). The scores were significantly correlated. The majority of patients had symptoms localised to the digit or point of injury. All but one of the five selected components of the CIQ and the separate impact score were significantly correlated. Conclusion: The authors found the CIQ to be a simple scoring system that is suited to clinical use. The CIQ has value as a research tool as it provides a method of categorising patients and of identifying patients suited to certain treatment methods. Furthermore, it may be a more informative tool in monitoring treatment as it is able to assess changes in pattern as well as overall score.